Investigating Asynchronous Online Communication: A Connected Stance Revealed - Susan J Wegmann; Joyce K. McCauley (Online Learning, 2014)
This research project explores the effects of altering the structure of discussion board formats to increase students’ engagement and participation. This paper will present the findings of a two-university, two-class research project in which asynchronous discussion board entries were analyzed for substance. By using oral discourse analysis techniques, the postings of two distinct structures of discussion board entries were analyzed. A baseline of typical student interactions was established by using an Open-ended discussion board assignment. Then the requirements were changed and an Experimental discussion board format was introduced on which students were placed into smaller groups and expected to enact a 3R pattern of Respond, React, and Reply. The ways in which students make their thinking visible were coded and tabulated. Findings suggest that a Connected Stance, identified by a high level of participation coupled with a high level of engagement, was an optimal online discourse pattern.